Recent advances in managing gastrointestinal stromal tumor [version 1; referees: 2 approved] - Florence Duffaud; Axel Le Cesne (F1000Research, 2017)
Constitutive activating mutations in KIT and platelet-derived growth factor receptor α (PDGFRα) are heavily involved in the pathobiology of gastrointestinal stromal tumors (GISTs). This disease has served as an effective “proof-of-concept” model for targeting gain-of-function kinase mutations in cancer. This review discusses the current standard of care in terms of pharmacotherapy in the management of localized and metastatic GISTs.